Analysis of Added Value and Marketing Characteristics of Japuh (Dussumieria acuta, C.V.) Pindang Fish Products at Mamah Haji UMKM in Pangandaran - Junianto, Junianto; Atmojo, Sigit Bekti; Khalilah, Jasmine; Setyaji, Tristan Eka (CELEBES Agricultural, 2025)
The added value and marketing characteristics of fish pindang are not only a matter of microeconomics, but also touch on social aspects, public policy and regional development.  Added value helps to know how much profit is obtained from the process of processing fresh fish into pindang.  The study of marketing characteristics provides an overview of how pindang products are consumed and distributed.   This study aims to determine the added value and marketing characteristics of pindang fish products at Mamah Haji.  This UMKM located in Cikembulan Village, Sidamulih District, Pangandaran Regency, West Java. The research method used is the survey method. Data was obtained through direct interviews at the production house. The results of the study showed that the added value generated from the pindang fish processing process was IDR 18,000 / kg with a value added ratio of 37.5% which is included in the medium category. The net profit of the business reached IDR 10,000 / kg and the percentage of business profit was 43.48% so that this business is capital intensive. The market segmentation of Mamah Haji UMKM's pindang fish products targets local people and tourists. The product has advantages in the form of a distinctive taste, soft bone texture and hygienic vacuum packaging. Pricing is based on production costs while promotion is carried out through word of mouth and social media methods and distribution activities are carried out directly to consumers.